Redescriptions and descriptions of new species of Austrostrongylus Chandler, 1924 (Nematoda: Trichostrongylina), from Australian marsupials with a comparative study of features of the synlophe - Durette-Desset, M. C.; Beveridge, I. (Zootaxa, 2012)
Redescriptions are provided of Austrostrongylus aggregatus Johnston & Mawson, 1940, A. chandleri Mawson, 1973, A.macropodis Chandler, 1924, A. victoriensis Cassone, 1983 and A. wallabiae Johnston & Mawson, 1939 from macropodidmarsupials from eastern Australia. Two new species are described: A. mawsonae sp. nov. from Wallabia bicolor(Desmarest) and A. smalesae sp. nov. from Macropus rufogriseus (Desmarest), M. fuliginosus (Desmarest), M. giganteusShaw and W. bicolor (Desmarest). A. paratypicus Mawson, 1973 is treated as a synonym of A. macropodis. The synlopheis described from serial transverse sections of males and females of each species and the origins and terminations of thecuticular ridges documented for use in specific identification. Females of some species could be distinguished only bydifferences in the synlophe. The geographical and host ranges of all know species are expanded based on newercollections. Based on a study of seven species, comments are provided on the remaining congeners. A. petrogaleBeveridge & Durette-Desset, 1986 and A. safestatus Beveridge & Durette-Desset, 1986 are removed to the genusSutarostrongylus Beveridge & Durette-Desset, 1986 as S. petrogale comb. nov. and S. safestatus comb. nov. Keys are provided to males based on the features of the spicules and to females based on features of the synlophe.